Court of the Moon, Golden Gate International Exposition, San Francisco (H.S. Crocker Co., Inc.)
Blue and amber lights directed on fluorescent blue paints produce the restful mood of the Court of the Moon at San Francisco's World's Fairs on Treasure Island. Music is played on a 40-bell carillon in the Tower of the Sun, tipped with a golden Phoenix, in background.